2011
DOI: 10.1016/j.jvs.2011.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Emergency stent graft implantation for ruptured visceral artery pseudoaneurysm

Abstract: Stent graft exclusion of visceral artery pseudoaneurysm seems to be a valid therapeutic approach regardless of the patient's septic or hemodynamic status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 36 publications
1
30
0
6
Order By: Relevance
“…As an alternative endovascular procedure, stent-grafts may be placed in the bleeding vessel in order to exclude the site of bleeding or pseudoaneurysm sac, as demonstrated in two of our cases (31,32). Considering that all complications in this study were associated with ischemic injury to the spleen after embolization of the splenic artery, the use of stent-grafts potentially decreases the likelihood of end-organ ischemia.…”
Section: Discussionmentioning
confidence: 90%
“…As an alternative endovascular procedure, stent-grafts may be placed in the bleeding vessel in order to exclude the site of bleeding or pseudoaneurysm sac, as demonstrated in two of our cases (31,32). Considering that all complications in this study were associated with ischemic injury to the spleen after embolization of the splenic artery, the use of stent-grafts potentially decreases the likelihood of end-organ ischemia.…”
Section: Discussionmentioning
confidence: 90%
“…of patients presenting with VAAs over a 10‐year period found that 50% of the detected gastroepiploic artery aneurysms were in fact pseudoaneurysms. Unlike true VAAs which are often caused by arteriosclerosis, systemic or portal hypertension, vasculitis or connective tissue disorders, visceral artery pseudoaneurysms (VAPAs) are often the result of abdominal trauma resulting in intimal damage and arterial wall weakening, vessel wall destruction due to proteolytic enzymes released during pancreatitis, and iatrogenic arterial injury during operative or percutaneous biliary interventions, and liver transplantation . None of these risk factors, however, were noted in our patient.…”
mentioning
confidence: 76%
“…The causes of visceral artery pseudoaneurysms are trauma, infection, inflammatory diseases, and complications of abdominal surgery, hepatobiliary interventions, and endoscopic explorations [5]. On the other hand, the incidence of pseudoaneurysms caused by malignant tumors is low although pseudoaneurysms caused by hepatocellular carcinomas (HCC), malignant lymphomas, desmoids, neurofibromatosis, giant cell tumors, leukemia, and so on have been reported [6][7][8][9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%